Análise do biogás utilizando a manipueira proveniente da casa de farinha de Itaporanga d’Ajuda/SE - Oliveira, Juliana Marçal de (2021)
In the manioc flour manufacturing process, an effluent called cassava wastewater is generated, generated when the moisture is removed from the grated dough. It has a high content of organic matter and carbohydrates that easily contaminate the environment, which can lead to contamination of the soil and water bodies, in addition to the mortality of animals that consume it. The production of biogas is an effective means to contain this pollution, however, in most cases, the purification process is necessary for the elimination of undesirable gases, generated in the process. Thus, for sustainable development to take place, a study is needed to elaborate processes to minimize the spread of pollution. In view of this, the objective of this research was to carry out a treatment process via anaerobic digestion that minimizes the damage caused by the effluent from the production of cassava flour on a bench scale by means of anaerobic digesters for the production of biogas. Based on adaptations of the existing literature, kitassatos of 500 ml and PET bottles of 250 ml were used in the procedure as anaerobic digesters capable of producing biogas, using the cassava wastewater collected from a flour house in the city of Itaporanga d 'Ajuda / SE as biomass, aiming at this treatment as an energy resource for flour houses. As a result of the laboratory analysis of the cassava wastewater under study, values were obtained, pH: 4.98; BOD: 1090.00 mg O2/L; COD>10,000.00 mg O2/L; total organic carbon: 32,300.00 mg C/L; total solids at 105 ° C: 67,280.00 mg/L; total fixed solids: 9,642.00 mg/L; total volatile solids: 57,640.00 mg/L; and quantitative starch: 1.35 g/100g. In the analysis of the biogas, results were obtained for the levels of CH4 and CO2, for the tests using the blank cassava wastewater the average was 11.68% of CH4 and 88.32% of CO2, while, with the concentrated manipueira of 2:1 the average of CH4 levels rose to 83.87% and CO2 decreased to 16.13%. Therefore, the present study showed favorable results for the production of biogas when using the concentrated 2:1 cassava wastewater, making this study serve as a basis for future research, favoring the environment and small producers of cassava flour.